Excoriate of the Terrorism Propaganda - Susantono, Abdilah; Zulkarnain, Zulkarnain (Budapest International Research and Critics University, 2022)
Terrorism propaganda in mainstream approaches and strategies is very stigmatising towards certain cultures and results in unclear targets. The controversy over the U.S. attack on Iraq during the presidency of G W Bush Jr. was related to the issue of international legitimacy and the mainstream conceptions of terror and terrorism, with their derivative products in the approach and strategy of the terrorism propaganda. This research presents critical views from the international community on the conception of terror and terrorism and highlights the policy of the war against terror. This research is qualitative research, with literature review and analysis method in the form of meta-analysis. The findings of this research are that many experts in the international community criticise the conceptions of terror and terrorism and propose other approaches that are considered fair and reasonable. That approach is cultural identification regarding acts of terror (the act of terror) whose emergence factors are stratified and the scope of ethnicity, nation-state, and the dominance of the giant business sector. This alternative approach can be a more just way of handling terror acts and solid moral, legal, and political basis.